2020
DOI: 10.3389/fbioe.2020.600032
|View full text |Cite
|
Sign up to set email alerts
|

Histological and Histomorphometric Evaluation of Applying a Bioactive Advanced Platelet-Rich Fibrin to a Perforated Schneiderian Membrane in a Maxillary Sinus Elevation Model

Abstract: BackgroundSchneiderian membrane (SM) perforation is a major complication of maxillary sinus elevation with simultaneous bone grafting, yet under this scenario there is no standard biomaterial that maximizes favorable tissue healing and osteogenic effects.PurposeTo compare the effect of advanced platelet-rich fibrin (A-PRF) and collagen membrane (CM) on a perforated SM with simultaneous bone grafting in a maxillary sinus elevation model.Materials and MethodsAfter perforation of the SM was established, 24 animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 62 publications
1
8
0
1
Order By: Relevance
“…Thus, in the 2 sinus membranes perforated during the surgery, these were repaired with L-PRF clots and behaved exactly the same as the cases without perforations, validating the idea of a natural regeneration and without complications. 2,16 It is important to highlight that this study has a 100% of the implants success, including the cases of sinus membrane perforation, observing no biological complications during 40 months of follow-up. This is similar the results by Dominiak et al, 17 which declared the use of PRF as filling material in maxillary sinus showed promising results.…”
Section: Discusionmentioning
confidence: 79%
See 1 more Smart Citation
“…Thus, in the 2 sinus membranes perforated during the surgery, these were repaired with L-PRF clots and behaved exactly the same as the cases without perforations, validating the idea of a natural regeneration and without complications. 2,16 It is important to highlight that this study has a 100% of the implants success, including the cases of sinus membrane perforation, observing no biological complications during 40 months of follow-up. This is similar the results by Dominiak et al, 17 which declared the use of PRF as filling material in maxillary sinus showed promising results.…”
Section: Discusionmentioning
confidence: 79%
“…Given the fragility of the sinus membrane, its rupture is a common complication during sinus lift and may preclude the use of particulate grafts. 2…”
mentioning
confidence: 99%
“…An advanced experiment joins the reviews above, managed by Xin and collaborators [ 41 ], which was able to display a total repairment of the perforated Schneiderian membrane and a greater amount of new bone formed under the area through the application of A-PRF in a sinus lift model.…”
Section: Discussionmentioning
confidence: 99%
“…As evidências do uso da fibrina rica em plaquetas e leucócitos no reparo das perfurações da membrana sinusal são limitadas. Estudos in vivo em modelo animal tem demonstrado sua efetividade favorável na reparação dessas perfurações comparando com membranas de colágeno e na formação óssea nas áreas enxertadas (Aricioglu, et al, 2017;Xin, et al, 2020).…”
Section: Discussionunclassified